In Person Online: What Trainee Psychotherapists Discovered About Online Clinical Work - Day, Elizabeth; Thomas-Anttila, Kerry (New Zealand Association of Psychotherapists (NZAP) Inc., 2021)
During the 2020 lockdown in response to COVID-19, students in the Master of Psychotherapy at the Auckland University of Technology (AUT) were required to rapidly move their clinical work online. We surveyed these students about their experience of working clinically online. We used a mixed-methods approach and analysed qualitative data using grounded theory methods. Students found the move online difficult, with technological challenges, the loss of a professional clinical space, and having to establish and maintain the therapeutic alliance in the unfamiliar online setting. They showed a strong preference for in-person clinical work, along with scepticism about the efficacy of online therapy, though some acknowledged its convenience and others its currency and relevance. Most expressed a need for more specific training in online therapy. Students rated their technological skill level higher than their levels of interest in online communication. This suggests that preferences, rather than technical skill, influenced their hesitancy for working clinically online. While online therapy can impose increased strain on clinicians and directly impact their capacity to manage online clinical work, the literature finds strong and consistent evidence that online therapy has equivalent outcomes to in-person therapy. There is significant emphasis in the literature on the disjunct between the outcomes evidence and therapist expectations. This is modified somewhat by training and experience in online therapy. We recommend that research- active psychotherapists engage actively and collaboratively with the profession, through professional bodies, to encourage research-informed professional development and practice for clinicians; and that further research is conducted into effective strategies for training in online clinical delivery.
Keywords: Clinical; In-person; Online therapy; Trainee psychotherapist; Student; COVID-19; Pandemic